2011
DOI: 10.1053/j.gastro.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin and p120 Mediate PPARδ-Dependent Proliferation Induced by Helicobacter pylori in Human and Rodent Epithelia

Abstract: Background & Aims Colonization of gastric mucosa by Helicobacter pylori leads to epithelial hyperproliferation, which increases the risk for gastric adenocarcinoma. One H. pylori virulence locus associated with cancer risk, cag, encodes a secretion system that transports effectors into host cells and leads to aberrant activation of β-catenin and p120-catenin (p120). Peroxisome proliferator-activated receptor (PPAR)δ is a ligand-activated transcription factor that affects oncogenesis in conjunction with β-caten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 27 publications
2
56
0
2
Order By: Relevance
“…Studies from two independent groups revealed that loss of PPARδ by deletion of its exons 4-5 or exon 4 reduced intestinal adenoma burden in both Apc Min/+ and AOM-treated mice without exposure to DSS (22,23). A recent report described a role of PPARδ in Helicobacter pylori-associated gastric carcinogenesis, which represents another example of its effects in a proinflammatory pathway (24). These results suggest that PPARδ has proinflammatory and protumor effects.…”
Section: Discussionmentioning
confidence: 88%
“…Studies from two independent groups revealed that loss of PPARδ by deletion of its exons 4-5 or exon 4 reduced intestinal adenoma burden in both Apc Min/+ and AOM-treated mice without exposure to DSS (22,23). A recent report described a role of PPARδ in Helicobacter pylori-associated gastric carcinogenesis, which represents another example of its effects in a proinflammatory pathway (24). These results suggest that PPARδ has proinflammatory and protumor effects.…”
Section: Discussionmentioning
confidence: 88%
“…H. pylori activates β-catenin through inactivation of GSK-3β, or via an interaction between CagA and membrane-associated β-catenin, which promotes mitogenic signalling and proliferation. 91213 …”
Section: Introductionmentioning
confidence: 99%
“…In addition to activating MAPK, H. pylori infection also induces the expression of other inflammatory responsive genes including nuclear factor-κB (NF-κB) (8), cyclooxygenase-2 (COX-2) (9) and aquaporin 3 (AQP3) (10). H. pylori has been reported to stimulate the proliferation of gastric epithelial cells both in vitro and in vivo (5,11,12) and to alter intercellular tight junctions (13), thus facilitating the malignant transformation of the gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%